Synthesis and characterization of N-type organic semiconductors and their potential applications in solar cells and sensors for sport - Chen, Wangqiao (2017)
During the past two decades, organic solar cells (OSCs) have attracted wide attention due to several advantages of light weight, low cost, easy processing and flexibility. Meanwhile, various usages of OSCs in wearable electronics recently imply the potential wide application of this technique in the area of sport. Growth of Power Conversion Efficiency (PCE) of OSCs has reached higher than 10% for single junction OSCs mainly through design and synthesis of novel donors (p-type semiconductors materials), optimization of film morphology and device development. However, one lagging area is the development of novel electron acceptors (n-type semiconductors materials).